Dynamics of the Community of Inquiry (CoI) within a Massive Open Online Course (MOOC) for In-Service Teachers in Environmental Education - Maya Kaul; Maija Aksela; Xiaomeng Wu (MDPI AG, 2018)
One of the greatest ways to transform education systems is to develop community-centered professional supports for in-service teachers. Given the rise of distance learning platforms such as massive open online courses (MOOCs), there is a growing potential to deliver such supports at scale. The community of inquiry (CoI) framework models the asynchronous, text-based communication that defines educational experiences within such collaborative learning environments; however, methods of CoI transcript analysis must be improved. This paper uses the University of Helsinki's 2016 MOOC, Sustainable Energy in Education, as a case study on how the CoI framework can be used to characterize the educational experience of in-service teachers in distance learning environments. Using the CoI coding protocol, this paper employs a transcript analysis of the discussion forum posts on the MOOC (n = 78), and applies improved measures of reliability in order to understand the capacity of CoI transcript analysis to reliably define online learning experiences. The findings suggest that, while the CoI framework is able to characterize some elements of online learning communities, more work needs to be done to ensure the framework captures the more nuanced elements of such educational experiences, such as the effects of course design and the relative engagement of course participants.